Incidence and profile of psoriasis in the dermatology-venereology department Bali Mandara General Hospital, Denpasar during 2020-2022 - Margha, Ni Putu Tiza Murtia; Rinawati, Ni Wayan Wendy (International Journal of Research in Medical Sciences, 2023)
Background: Psoriasis is a chronic inflammatory disease mediated by the immune system that mainly involves skin inflammation, epidermal hyperplasia, enriched risk of destructive arthritis, and cardiovascular morbidity. Accurate epidemiology of psoriasis is limited, just very few studies on the incidence of psoriasis. This study aims to determine the incidence and profile of psoriasis patients at the dermatology and venereology polyclinic, Bali Mandara General Hospital Denpasar Bali, 2020 to 2022. Methods: This research is a descriptive cross-sectional retrospective study at the dermatology-venereology polyclinic of Bali Mandara General Hospital Denpasar from May to June 2023 and uses secondary data from the patient register book and medical records with total sampling. Samples were all new cases that met the inclusion and exclusion criteria would be sampled. Data were analyzed with statistical package for the social sciences (SPSS) 28 for Windows, categorized by numbers and percentages, providing cross-tabulations for age and sex variables. Results: Psoriasis was grouped into five types. Psoriasis vulgaris is the most common type with total of 71 (85.5%) patients, guttate psoriasis 6 (7.2%), sebopsoriasis 5 (6.0%) patients, pustular psoriasis 1 (1.2%) patients, and psoriasis erythroderma 0 (0%) patients. Conclusions: Psoriasis vulgaris is the most common type of psoriasis. It occurs more frequently in the age, 20-30 to 50-60 years. According to studies, the incidence of psoriasis by sex between males and females is equally the same. We present data categorized by numbers and percentages, providing cross-tabulations for age and sex variables.